Richness and activity of arthropodophagous bats in an arid landscape of central México - MacSwiney González, María Cristina; Ávila-Flores, Rafael; Pech Canché, Juan Manuel (THERYA, 2019)
The insectivorous bats of arid and semi-arid ecosystems have been poorly studied in México. The aim of this work was to determine the richness and activity of insectivorous bats in arid landscapes of central México over an annual cycle and identify the landscape and environmental features related to relative abundance patterns of bats. We carried out captures with mist nets and active acoustic monitoring in 10 transects, semi-active monitoring in eight stations, and passive monitoring in two desert grassland and scrub sites in Aguascalientes and Jalisco, from January to December 2012. The activity index of each insectivorous species was calculated and related to the local features at the landscape level. An automated monitoring weather station was established in the study area to explore the potential effect of environmental conditions on activity through time. Two species of insectivorous bats were captured: Myotis melanorhinus and Myotis occultus; seven additional species belonging to three families were acoustically identified, with Tadarida brasiliensis as the most active species. Activity levels were concentrated during the spring (April-June) and from mid-summer to late fall (August-October). The null activity in winter (January-March) and the increased activity of T. brasiliensis in the spring suggest migratory movements of the species in the region. The highest values of the activity index were recorded in the proximity of water bodies and ravines. Overall activity was recorded at temperatures between 6.8 and 20.3 Â°C, and under wind speeds between 1.6 and 24.1 km/h.